Representation of Women in the Wedding Industry Media: A Critical Discourse Analysis of the Bridestory's Instagram Narratives - Vir Risky Kustiani (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2022)
Women are the main object in the institution of marriage. For the wedding industry, narratives about women are commodified into a product that has a high exchange value in this industry. This article discusses how the wedding industry uses the media to represent women and play a role in spreading the pleasure that is considered "most" for women, namely marriage. The wedding industry propagates the image of glorifying the ideal bride. Sara Mills' critical discourse analysis model is for interpreting messages conveyed by wedding industry professionals through social media. Data was collected from professional Instagram narratives related to the wedding industry. The findings show how the constructs are built to determine the position of the subject-object and readers regarding the wedding industry. The constructed image of the ideal marriage occupies the subject position. It defines women in the object position to achieve feminine marriage ideals in the name of self-empowerment by celebrating various choices. The reader's position is marked by perceiving the marriage experience from the representation of women presented by the media. In the end, these positions give the highest social status to married women and provide the legitimacy that women need to marry but still feel like active agents in their lives. This hegemony ultimately strengthens the progress of the marriage industry.